Problem Solving Skills and their Related Factors in Nursing Students - Leili Feizi Konjini; Reihaneh Fadakar Soghe; MinooMitra Chehrzad; Ehsan Kazemnejad- Leili (Guilan University of Medical Sciences, 2016)
Abstract Introduction: Depression during pregnancy is among the most important types of depression in women, which can have serious consequences for both mother and child. Objective: Therefore, this study aimed to determine the prevalence of depression and its effective factors in pregnant women attending health centers in Neyshabur in 2013. Methods: This cross-sectional descriptive and analytic study was conducted on 280 pregnant women referring to health centers in Neyshabur in 2013. Five of nine health centers were randomly selected using cluster sampling method. Sample size was determined considering ratio data and the referrals to each center using random systematic method. They were enrolled after obtaining verbal consent. In this study, data collection tool was a two-part questionnaire. First part consisted of demographic information (age, number of previous deliveries, gestational age (in weeks), pregnant woman's job, year(s) of marriage, family monthly income, age difference with husband, pregnant women's education, spouse's education level, abortion history, planned or unplanned pregnancy, personal or family depression history). Second part contained Beck Depression Inventory with 21 items which measures physical, behavioral and cognitive symptoms of depression. Each question has four options that can be scored from 0 to 3 and each item specifies various degrees of depression from mild to severe. Total range of its scores ranges between 0 to 63. Scores less than 10 represent a normal status, 11- 16 mild depression, 17-20 need consultation with psychologist or a psychiatrist, 21-30 relative depression, 31-40 severe depression and more than 40 very severe depressions. Since the onset of some symptoms such as sleep disorders, weight fluctuations and energy reduction can exist in a normal pregnancy, diagnosing depression may be difficult. Although developing depression score is considered to be higher than 10, scores higher than 16 were considered as the threshold of depression in pregnant women. Descriptive and inferential statistics were used to analyze the data. For univariate analysis, chi-square was determined to compare the qualitative variables. T-test and Mann–Whitney test were used to compare the quantitative and ordinal variables, respectively. Moreover, logistic regression model (Backward) was used to examine the relationship between study variables and depression. Significance level was considered less than 0.05. Results: The mean age of the patients was 25.5 ± 5.24 years. 135 (48.2%) of the 280 women were under 25 years of age. 55 cases had (19.6%) less than high school education. 158 women (56.4%) experienced their first pregnancy. 53 cases (19.9%) were in their first trimester of pregnancy. In this study, 84 (30%) of pregnant women had some degrees of depression symptoms. 50 of them were under 25 years (59.5%) and 34 (40.5%) were over 25 years old. 46.2% of women whose family monthly income was less than or equal to 150 $, and 24.5% of women with income above this amount had symptoms of depression. Furthermore, 25.3% of women with planned pregnancy and 74.1% of those with unplanned pregnancy had symptoms of depression. Using the chi-square test, a statistically significant relationship was observed between age, pregnant woman's job, monthly family income, level of education, spouse's education level, planned or unplanned pregnancy with symptoms of depression during pregnancy (p<0.05). Yet, other variables (number of previous deliveries, gestational age, year(s) of marriage, age difference with husband, abortion and depression history) were not significantly associated with symptoms of depression during pregnancy (p>0.05). Finally, using multivariate logistic regression model showed a significant relationship between age of pregnant women (P<0.001, OR =0.35), family monthly income (P<0.00, 1, OR =0.32) and planned or unplanned pregnancy (P<0.001, OR =11.66) with symptoms of depression during pregnancy. Conclusion: In attention to study findings, it seems that pregnant women's depression level in Neyshabur is high. Therefore, it is suggested that managers of therapeutic health care centers implement appropriate interventions in order to reduce or prevent depression during pregnancy.